Controlador Difuso Inteligente para un Cargador de Baterías de Plomo-ácido - Guacaneme Moreno, Javier Antonio; González Beltrán, Danny Alejandro; Trujillo Rodríguez, César Leonardo (Ingeniería, 2002)
Abstract During the last ten years, Fuzzy Control has become the most popular method for controlling non-linear processes, due to its implementation simplicity, robustness and lack of a rigurous mathematic presentation. A fuzzy controller for a lead acid battery charger is studied in this paper. Effective control of the charging process is complex because of the exponenetial relationship between the charging time and current. Classic control algor ythms are difficult to implement because the value of the discharge coefficient is unknown in the current-time exponenetial relationship. A microcontroller based digital architecture is developed; its task is to regulate the battery charging process through a Fuzzy Inference System which output changes the trigger angle of a Power Switch.